Compatibility and mechanical properties of biocomposite polymer, derived from palm oil empty fruit bunch as the reinforcement material / Rosman Senawi - Senawi, Rosman (2014)
Traditional composite are reinforced with inorganic fibers which is expensive and harmful to the environment. In recent years, composites o f polymer reinforced natural fibers have received much attention as they offer advantages as compared with inorganic fillers in terms of cost and biodegradability. Empty Fruit Bunch (EFB) fibers were selected as reinforcement for this research due to the renewable, low cost, low density and its have a similar structure like natural fiber. To fulfill the biodegradable properties of the composites, Polylactic acid (PLA), a type o f biopolymer was selected as the matrix. To enhance compatibility and improve interfacial adhesion between the fiber and the matrix, the fiber surface must be pretreated with chemicals or coupling agents. Therefore, six different chemical treatments were used in this research; NaOH, silane and NaOH/silane, NaOCh, NaOC12/silane and NaOC12/NaOH treatment. Thus, the objective o f this research is to evaluate the effect o f fiber surface treatments and fiber loading on the mechanical, thermal and morphology of PLA/EFB biocomposites. The best treatment is then selected and two types of additives were added. The first one is diphenylmethane-4, 4'-diisocyanate (MD1) known as a coupling agent and the other is triallyl isocyanurate (TAIC), one crosslinking agent. Both biocomposites samples were irradiated using electron beam and the effect of radiation to the properties o f the biocomposites was studied. The testing results revealed that the mechanical, thermal and morphology of the biocomposites using treated fiber were improved compared with untreated fiber. The best surface treatment for the EFB fiber is NaOH/silane and the optimum fiber loading was achieved at 10 wt%. The addition of MDI and TAIC improved the mechanical and thermal properties also the morphology. However after irradiation, TAIC shows better results for mechanical and thermal properties as well as morphology o f the biocomposites compared with MDI.